Adaptation of New Normal Community in the Coronavirus Pandemic Situation in Surat Thani Province - Jariyawijit, Benya; Nak-pin, Siyathorn (Chophayom Journal, 2023)
This research project aimed to explore the impact and adaptation of people in the situation of the coronavirus (COVID-19) epidemic towards the adaptation of the new normal community in Surat Thani Province. The study is quantitative research and using questionnaire as data collection tool. Using random sampling from people in 3 districts, namely, Mueang Surat Thani, Koh Samui and Ban Na Doem. The collected data were analyzed using descriptive statistics consisting of percentage and hypothesis testing using F-test and t-tests to make the comparisons. The results of the research showed that 1) comparison of the first and subsequent outbreaks of COVID-19, it was found that the impact on the economy was greater in all aspects. In terms of health, there was more infection prevention and health care, while there was an increase in stress/anxiety compared to normal situations. In terms of social and environmental aspects, the COVID-19 situation did not affect the relationship of household members. In the field of information technology, most people have access to the same information sources, however, new technologies are being learned while the risk of perceiving false information increases. And in terms of education, online learning and the cost of online learning were the issues that had the greatest impact on households. 2) the adaptation of the people, in terms of economy, most of them continue to operate the same business and do not develop themselves by creating or upgrading their existing skills. However, there is an adaptation using online self-learning and home cooking. In terms of health, there is an adaptation by emphasizing on eating freshly cooked food, washing hands with water and soap or alcohol gel, and wearing a mask. On the social and environmental aspect, the use of social media and the use of telephones increases, while in the field of information technology, there is an adaptation by learning to use communication devices on their own, and in terms of education, there is an adaptation by allowing family members to allocate the most time to teach and take care of their children. Keywords: Community-based adaptation, new normal communities, COVID-19